WORLD BANKING SYSTEM: POST-CRISIS RECOVERY? - BULATOVA, Olena; MARENA, Tetyana (Journal of European Economy, 2019)
The article studies the state of the world banking system recovery after the global crisis. It is stated that by the indicators of financial depth, capital adequacy and profitability of the biggest banks the world banking system is nowadays the most stable and profitable for the entire post-crisis period of its development. It is noted that the structure of the modern world banking system corresponds to the spatial structure of the world economy, which consists of different taxonomic levels of regions and where the role and importance of global regions is being enhanced against the background of the globalization processes deepening. Based on the study of changes in the distribution of bank assets and banks’ profits between global regions, the rankings of the biggest banks in the world, indicators of return on assets and return on equity of banks from different regions, regional peculiarities of mergers and acquisitions in the banking sector, progress in the implementation of the requirements of the Basel Committee on Banking Supervision, regional features of the post-crisis recovery of the world banking industry are identified. It is proved that there is an increasing degree of unevenness in distribution of bank assets between global regions, and a tendency of increasing bank assets concentration in three main regions – Asia Pacific, American and European regions – is found out. On the basis of assessment of the transformational shifts in the regional structure of the world banking industry changes of the global regions role in the world banking system in the process of its post-crisis recovery are identified. JEL: G15, G21.